A comunidade de Curculionidae (Coleoptera) de inflorescências da palmeira Euterpe longebracteata Barb. Rodr. em uma área de transição Amazônia-Cerrado, Mato Grosso, Brasil - GUIMARÃES, José Raimundo Rocha (Universidade Federal do Pará, 2013)
The research was done with the community Curculionidae inflorescences of the palm Euterpe longebracteata in riparian areas (PPAs), degraded and preserved, in Tanguro Farm, Mato Grosso, Brazil, aiming to provide inputs on policy management and recovery areas. The weevils represented the most important component of the fauna associated with the inflorescences of the E. longebracteata, with 23 species richness, frequency of 97% in the samples and abundance of 10,000 (or 90% of total abundance). Species Phyllotrox sp. 18, Phyllotrox sp. 19, Erirhininae gen.n.Asp.1 , Erirhininae gen.n.Esp.1 and Bondariella sp. 3 accounted for more than 98% of abundance, were found to be dominant in the inflorescences of E. longebracteata and therefore specifically related to the palm and can act as effective pollinators species of the E. longebracteata in the area. Despite the differences between PPAs preserved and degraded populations of E. longebracteata and species composition of Curculionidae were not correlated with the level of degradation of PPAs. The wealth of Curculionidae also not correlated with canopy cover, distance to the edge of the sample, size of inflorescences and number of flowers per inflorescence of E. longebracteata. The influence of collection period on the abundance of most dominant species was regarded as indicative of population dynamics and ecological succession. While Phyllotrox sp. 19, seems to present a pattern of aggregate distribution. Species Phyllotrox sp.18 and Erirhininae gen. No The sp. 1 were considered as having plenty more sensitive to degradation of PPAs. The palm E. longebracteata has potential use in the recovery of degraded areas of Tanguro farm because their populations and species of Curculionidae likely pollinators showed tolerance to the observed degradation.